2018
DOI: 10.1111/jfbc.12539
|View full text |Cite
|
Sign up to set email alerts
|

Structure-function properties of hypolipidemic peptides

Abstract: This review addresses the structure-function properties of hypolipidemic peptides. The cholesterol-lowering peptide (lactostatin: IIAEK) operates via a new regulatory pathway in the calcium-channel-related mitogen-activated protein kinase (MAPK) signaling pathway of cholesterol degradation. The bile acid binding peptide (soystatin, VAWWMY) inhibits the micellar solubility of cholesterol in vitro and cholesterol absorption in vivo. VVYP is the most effective peptide having hypotriglyceridemic action in globin d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 53 publications
0
30
0
Order By: Relevance
“…By checking the reabsorption of bile acids within digestive organs, soy peptides (i.e., lactostatin (IIAEK)) can effectively lower blood cholesterol levels, thus effectively decreasing LDL and fat accumulation ( Figure 12 ), which enables their use in preventing and treating arteriosclerosis [ 5 ]. Soy proteins also contain angiotensin-I converting enzyme (ACE-I)-inhibiting peptides that decrease blood pressure levels ( Figure 13 ), as well as antithrombotic peptides that inhibit platelet aggregation [ 149 , 150 ]. The diverse effects of soybean-derived bioactive peptides are summarized in Table 2 .…”
Section: Soy Proteins and Peptidesmentioning
confidence: 99%
“…By checking the reabsorption of bile acids within digestive organs, soy peptides (i.e., lactostatin (IIAEK)) can effectively lower blood cholesterol levels, thus effectively decreasing LDL and fat accumulation ( Figure 12 ), which enables their use in preventing and treating arteriosclerosis [ 5 ]. Soy proteins also contain angiotensin-I converting enzyme (ACE-I)-inhibiting peptides that decrease blood pressure levels ( Figure 13 ), as well as antithrombotic peptides that inhibit platelet aggregation [ 149 , 150 ]. The diverse effects of soybean-derived bioactive peptides are summarized in Table 2 .…”
Section: Soy Proteins and Peptidesmentioning
confidence: 99%
“…The ingestion of whey protein was observed to be correlated with a significant reduction in total cholesterol levels in rats fed cholesterol-free and cholesterol-enriched diets [53]. The cholesterol reducing activity of β-lactoglobulin was due to the presence of two major biopeptides, namely lactostatin (IIAEK) and β-lactotensin (HIRL) [54]. According to the literature, consumption of 300 mg IIAEK × kg −1 body weight per day reduced LDL level as well as increased HDL cholesterol level, and fecal steroid excretion.…”
Section: Hypocholesterolemic Peptidesmentioning
confidence: 99%
“…Despite the optimistic results, it should be noted that the exact mechanisms of the hypocholesterolemic activity of peptides are still unclear. It is speculated that it might be linked to the amino acid composition, but further research is needed in this respect [54].…”
Section: Hypocholesterolemic Peptidesmentioning
confidence: 99%
“…Nagaoka S. et al found for the first time that VAWWMY (soystatin) derive from soybean glycinin acted as an inhibitor of cholesterol absorption in vivo [13]. There are so many in vitro active soypeptides, soystatin is an only in vivo active hypocholesterolemic peptides derived from soybean [14]. Given the growing requirements for daily preventive therapies for lifestyle related diseases, hypolipidemic peptides could yield new avenues for medical dietary interventions.…”
Section: Introductionmentioning
confidence: 99%
“…Given the growing requirements for daily preventive therapies for lifestyle related diseases, hypolipidemic peptides could yield new avenues for medical dietary interventions. Notably, the use of such naturally occurring peptides should be more safe and effective than protein hydrolysates [14][15][16][17][18], which contain multiple unknown components in addition to the active molecules.…”
Section: Introductionmentioning
confidence: 99%